Liverwort diversity in China: spatial and taxonomic patterns on species richness - Cui, Jiaqi; Yang, Xiuhua; Li, Xiaoyu; Li, Jitong; Dong, Siqi; Wang, Hongfeng; Yang, Chengjun (Frontiers in Plant Science, 2024)
On the basis of records from national and provincial liverwort lists, herbaria and online databases, a dataset of liverwort distributions was created to analyze the geographical distribution patterns of liverwort species diversity in China. According to the taxonomy of liverwort species in the CoLChina database, more than 60,000 distribution records of 34 provincial geographic units were standardized. ArcGIS 10.8 was used to map the overall richness of liverwort species, as were the individual maps of 14 taxonomic groups of liverworts. Southwest China presented very high species richness, followed by Central China and South China, which presented relatively high species richness. The centers of liverwort species diversity in China are highly consistent with the diversity centers of endemic liverwort in China, many sites from coastal areas to Mountains. The specific distribution centers include the Yunnan-Guizhou Plateau, Hengduan Mountain Range, coastal areas in southern China and Taiwan Mountain Range, as well as the Qinling Mountains and Taihang Mountains in the central region and the Changbai Mountains and Xiaoxing'an Mountains in northeast China. There was significant difference in the distribution patterns of liverwort groups among the different provincial regions in China. As large groups, Jungermanniales and Porellales are absolutely dominant, their distribution patterns are similar to the overall richness of liverwort. The distribution center of Jungermanniales is punctate, while the distribution center of Porellales is flaky. However, the diversity centers of the small and medium liverwort groups are abundant, and their distribution patterns are also significantly different, such as, Marchantiales and Metzgeriales are medium-sized taxa. There were five types of small groups. This study will help us record and understand the biogeographic patterns of liverwort, clarify the geographical distribution of the major phylogenetic groups (order) of liverwort, and analyze the geographical distribution of national endemic and provincial endemic liverworts in China, providing a theoretical basis for future assessments of conservation gaps and reasonable conservation actions for liverworts.